Some classes of surfaces generated by Nielson and Marshall type operators on the triangle with one curved side: Dedicated to Professor Gheorghe Coman on the occasion of his 80th anniversary - CĂTINAȘ, Teodora (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
We construct some classes of surfaces which satisfy some given conditions, using some Hermite, Nielson and Marshall type interpolation operators defined on a triangle with one curved side. Mathematics Subject Classification (2010): 41A05, 41A36, 65D05.